A cloud security audit quality model for a commercial bank in Malaysia - 601603 Mariana Md. Hashim, 1982- , author; Mazdak Zamani, supervisor; Sekolah Informatiks Termaju 506658 (Kuala Lumpur : Universiti Teknologi Malaysia, 2014)
Thesis (Sarjana Sains (Jaminan Maklumat)) - Universiti Teknologi Malaysia, 2014